2020
DOI: 10.1371/journal.pone.0229970
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in Fly-In-Fly-Out employees in the Australian resources sector: A cross-sectional study

Abstract: BackgroundWorkplace bullying has diverse consequences at both the organisational and individual level. Anecdotal reports indicate that workplace bullying is an issue of particular concern for Australian FIFO workers, which may impact on psychosocial distress. However, no prior studies have examined this issue empirically in a FIFO worker cohort. Methods and materialsA cross-sectional survey study design was used to establish the prevalence of bullying in Australian FIFO, antecedents of bullying, and its associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
(125 reference statements)
0
6
0
2
Order By: Relevance
“…The majority of participants in the studies were men (averagely 91.2%), and all were aged between 16 and 68 years (mean of study means=39.23±4.29 years). The majority (89.25%) of studies were rated medium to high on the JBI Quality Rating Scale: 58 of 90 studies, for example, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] rated ≥70% (high), 23 studies, for example, 18 44-49 rated 50%-69% (medium), and 9 studies, for example, 17 50-57 rated <50% (low) (table 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of participants in the studies were men (averagely 91.2%), and all were aged between 16 and 68 years (mean of study means=39.23±4.29 years). The majority (89.25%) of studies were rated medium to high on the JBI Quality Rating Scale: 58 of 90 studies, for example, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] rated ≥70% (high), 23 studies, for example, 18 44-49 rated 50%-69% (medium), and 9 studies, for example, 17 50-57 rated <50% (low) (table 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…83 Stigmatisation and bullying Five cross-sectional studies identified workplace bullying to be associated with poor mental health outcomes. 41 42 52 62 73 Two studies documented workers who experienced workplace bullying were more likely to have high levels of suicide risk (OR=2.70; 95% CI=1.53 to 4.76), clinical depression (OR=2.38; 95% CI=1.40 to 4.05) 41 and psychological distress (OR=1.49; 95% CI=1.07 to 2.10) 62 than those who did not. Likewise, one study found increase in workplace bullying was associated with increased level of anxiety.…”
Section: Social Supportmentioning
confidence: 99%
“…Third, bullying is likely related to the blending of work and life while FIFO workers are away from home. We include bullying here as this was identified by a number of studies on FIFO work arrangements as an issue that affects worker mental health negatively (Sellenger & Oosthuizen, 2017; Miller et al, 2019; 2020). Bullying constitutes the repeated exposure to behaviour that is experienced to be intimidating, humiliating, or frightening (Leymann, 1996).…”
Section: Blending Of Work and Personal Lifementioning
confidence: 99%
“…We identified seven studies that statistically linked specific work and workplace attributes of FIFO workers with mental health outcomes. A survey study (Miller et al, 2020) identified social support as being positive for workers' mental health. In a survey study, Gilbert (2019) identified sense of community on site, as well as key work arrangement factors (including social aspects of the work environment, company support to attend to non-work issues, satisfaction with current work position, and quality of accommodation), as predictors of better mental health outcomes amongst FIFO workers.…”
Section: Predictors Of Mental Health Amongst Fifo Workersmentioning
confidence: 99%
See 1 more Smart Citation